Modulation of innate and adaptive anti-tumour immune responses - Lysaght, Joanne (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
Cancer is the second leading cause of death in the developed world after cardiovascular disease, with almost 25 million people living with cancer worldwide. The three main therapeutic approaches for the treatment of cancer involve one or more of the following, surgical removal, radiotherapy or chemotherapy. While effective against certain cancers, these therapies often have limited success. Therefore the development of novel and potent immunotherapies may provide more effective means of controlling malignant disease. Immunotherapeutic approaches are being developed as alternative or adjuvant therapies and clinical studies have shown that the manipulation of the immune system can modify tumour progression.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin